'Beginning wherever you wish': Sappho, Homer and the Homeric Hymn to Demeter in Theresa Hak Kyung Cha's Dictée. (20th January 2023) - Johnston, Paul G
Abstract: Theresa Hak Kyung Cha's Dictée expresses, in experimental and avant-garde form, the fragmented, disrupted and multilinguistic experiences of its author and her family against the tumultuous backdrop of twentieth-century Korean history. In the decades since its publication, the text has become established as a cornerstone of Asian American literary studies. This essay reads Dictée through the lens of its engagement with the ancient Greek classics, identifying how Cha responds to Sappho, Homer and the Homeric Hymn to Demeter in the context of her subversive and irreverent poetics. It demonstrates the important role that the Western classical tradition plays in Dictée as a structural and communicative resource for Cha's expression of her migratory identity as a Korean refugee in the United States. Cha engages with some of ancient Greece's most canonical texts from a direction that is radically askew from the typical approaches of classical scholarship, mediated in part by twentieth-century writers like James Joyce and Monique Wittig, advancing understandings of classical material that are feminist, anti-imperial and non-Eurocentric. Dictée should be recognized not just as a landmark of Asian American literature, but also as one of the most original creative responses to Greco-Roman antiquity of the late twentieth century.